Mexiletine in the treatment of LQT2, LQT3, and acquired LQTS: ameta-analysis - Dhiya Ihsan Ramadhan; Mohammad Iqbal; Charlotte Johanna Cool; Chaerul Achmad; Miftah Pramudyo; Hawani Sasmaya Prameswari; Mohammad Rizki Akbar (Jurnal Kardiologi Indonesia, 2026)
In “Mexiletine in the treatment of LQT2, LQT3, and acquired LQTS: a meta-analysis” (Indonesian Journal of Cardiology, 46(2), 71-79. https://doi.org/10.30701/ijc.1835), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1835. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. The publisher apologizes for any inconvenience caused by this error. DOI of original article: https://doi.org/10.30701/ijc.1835